Caracterización de experiencias de aprendizaje personalizado en el desarrollo de la motricidad fina en educación inicial i en la escuela Cesar Francisco Naranjo Rumazo “Semillitas” en el cantón Pujilí - Chicaiza Chicaiza, Mayra Cristina (2017)
The project is framed in fine motor skills, therefore it is necessary to collect, identify and analyze the characterizations of personalized learning experiences in the development of the fine motor skills of the child and initial education I in the Pujilí canton. In this way, this project was established in the "CESAR FRANCISCO NARANJO RUMAZO" SEMILLITAS School of Initial Education in Pujilí, a parish: Pujilí, belonging to the province of Cotopaxi, benefiting the entire educational community, such as children, Teachers and parents, during the year 2016, a methodology based on the search for tools has been applied that have allowed a collection of information both bibliographical and field that after the application and analysis have been fundamental pillar to discover the causes and Effects of the problem raised in that it highlights the lack of development in the fine motor skills of the children of Initial Education I both in the home and in the school due mainly to the lack of techniques and methodological strategies that allow the work with the Children to motivate them to continue discovering and developing on their own the fine motor skills. Another important aspect of the teaching-learning process is to develop fine motor skills on a daily basis so that in the future the child will have a greater ability to use the pencil, thus ensuring that the child feels safe and confident....